Update: Laser – an Everyday Tool with Underrated Risks - Hohberger, Bettina; Schünemann, Melanie; Sperlich, Karsten; Stahnke, Thomas; Berlien, Hans-Peter; Jakobs, Frank M.; Weinand, Frank Stephan; Reidenbach, Hans-Dieter; Schottenhamml, Julia; Stachs, Oliver (Klinische Monatsblätter für Augenheilkunde, 2025)
Lasers are present in nearly every aspect of modern life – in daily activities, medicine, and industry. While this innovative technology offers great benefits to society, it can also be misused, whether intentionally or unintentionally. Globalisation has fostered rapid development and wider distribution of high-energy lasers, including illegal trade and unregulated use, and has resulted in a rising number of laser-related eye injuries in recent years. This review addresses these concerns and compiles current knowledge on the subject. It begins with an overview of laser basics and historical milestones, then examines the physical and biological fundamentals of laser–tissue interactions. We discuss the latest laser innovations and the challenges they pose in introducing new technologies. An up-to-date overview of relevant laws and DIN standards for ophthalmic laser applications is provided, followed by a clinical perspective on laser attacks in civilian and military contexts and strategies for eye protection. The aim is to raise awareness of the potential risks associated with everyday laser use and to highlight the importance of safety measures alongside the many uses of lasers.
Keywords: ophthalmology; eye; retina; laser; safety